Androgen Receptor and Non-Coding RNAs’ Interaction in Renal Cell Carcinoma - Manal A. Hussain; Noha M. Elemam; Iman M. Talaat (Non-Coding RNA)
Renal cell carcinoma (RCC), the most prevalent among the urogenital cancers, accounts for around 3% of new cancer cases worldwide. Significantly, the incidence of RCC has doubled in developed world countries, ranking it as the sixth most common cancer in males, who represent two-thirds of RCC cases. Males with RCC exhibit a higher mortality rate and tend to develop a more aggressive form of the disease than females. Sex-related risk factors, including lifestyle and biological variations, explain this difference. The androgen receptor (AR) oncogenic signaling pathway has been extensively studied among the biological factors that affect RCC. Recent advancements in high-throughput RNA sequencing techniques have underscored the significant roles played by noncoding-RNAs (ncRNAs), previously dismissed as “junk”. The oncogenic potential of AR is manifested through its dysregulation of the ncRNAs’ availability and function, promoting RCC tumorigenesis. This review offers a summary of the most recent findings on the role and molecular mechanisms of the AR in dysregulating the ncRNAs that play a role in the progression of RCC and the possibility of utilizing ncRNAs to target AR as a potential therapeutic strategy.